Next-Generation Sequencing Identifies Pathogenic Variants in HGF, POU3F4, TECTA, and MYO7A in Consanguineous Pakistani Deaf Families - Xueshuang Mei; Yaqi Zhou; Muhammad Amjad; Weiqiang Yang; Rufei Zhu; Muhammad Asif; Hafiz Muhammad Jafar Hussain; Tao Yang; Furhan Iqbal; Hongyi Hu (Neural Plasticity)
Background. Approximately 70% of congenital deafness is attributable to genetic causes. Incidence of congenital deafness is known to be higher in families with consanguineous marriage. In this study, we investigated the genetic causes in three consanguineous Pakistani families segregating with prelingual, severe-to-profound deafness. Results. Through targeted next-generation sequencing of 414 genes known to be associated with deafness, homozygous variants c.536del (p. Leu180Serfs∗20) in TECTA, c.3719 G>A (p. Arg1240Gln) in MYO7A, and c.482+1986_1988del in HGF were identified as the pathogenic causes of enrolled families. Interestingly, in one large consanguineous family, an additional c.706G>A (p. Glu236Lys) variant in the X-linked POU3F4 gene was also identified in multiple affected family members causing deafness. Genotype-phenotype cosegregation was confirmed in all participating family members by Sanger sequencing. Conclusions. Our results showed that the genetic causes of deafness are highly heterogeneous. Even within a single family, the affected members with apparently indistinguishable clinical phenotypes may have different pathogenic variants.